Analysis of Taiwanese undergraduates' learning and development of TPCK in English instruction. (2015) - Chien, Chin-Wen
This study analyses 30 Taiwanese undergraduates' construction and development of technological pedagogical content knowledge (TPCK) in English instruction in a language teacher education program in a northwestern university in Taiwan. Data included class projects, surveys, and interviews. This study has these findings. First, the participants became aware of different types of multimedia tools through the instructor's demonstration and modelling and their own hands-on experiences and manipulation. Their TPCK was developed and constructed through the evaluation of multimedia tools, lesson plans and activity designs, group and class discussions, and personal reflections. Suggestions regarding course design on developing undergraduates' TPCK are provided.